Olive Oil in Antiquity. Israel and neighbouring countries from Neolith to Early Arab period - Heltzer, Michael (1987)
Conference; December, 1987, Haifa. University of Haifa. Israel Oil Industry Museum. Dagon Museum. Sponsored by: The Culture & Art division Ministry of Education & Culture, Shemen Industries Ltd., Miloumor-Milouot Ltd., Research Fund of Israel Edible-Oil Industry